Idioms in the literary works of the Slovenian writer Drago Jančar - Rojs, Jurij (Jezikoslovni zapiski, 2015)
This article presents the structure of idioms in some selected works by thewriter Drago Jančar. Most of them have the structure adjective + noun, followed by the structure verb + noun and verb + preposition + noun. Many of the author’s idioms and quotations come from various languages, primarily Latin, and fewer are folklorisms, ellipses, swearwords, phonetic words, interjections, and transformations of phrasemes.